Changes in coagulation functions and hemorheological parameters may predict hematoma formation after total knee arthroplasty. Issue 1 (December 2016) - Liu, Ning; Luo, Simin; Hang, Cheanglek; Zha, Zhengang; Li, Jieruo; Wu, Wenrui; Hou, Dabiao
Abstract Background Hematoma formation around the knee is commonly seen after total knee arthroplasty (TKA) and may cause patient discomfort and worry regarding the success of the surgery. This study aimed to evaluate the coagulation functions and hemorheological parameters in patients undergoing TKA and investigate their associations with hematoma formation. Methods This study prospectively included 146 patients treated for knee osteoarthritis by unilateral TKA between August 2013 and August 2014. Apixaban was administered twice during the 12–24-h period after surgery. Blood coagulation functions were evaluated according to activated partial thromboplastin time (APTT), prothrombin time (PT), thrombin time, and fibrinogen preoperatively and on postoperative days 1, 3, 7, and 14. Hemorheological parameters were also measured. Patients were divided into a hematoma group and a non-hematoma group for comparison. Results On postoperative day 1, the hematoma group showed significantly prolonged APTT and PT and significantly decreased hematocrit relative to baseline values (P  < 0.05). The whole blood high shear rate, whole blood low shear rate, plasma viscosity, and hematocrit did not differ significantly between the two groups at baseline or from postoperative days 1–14 in (P  > 0.05). Conclusions Prolonged APTT and PT on the first day after TKA as well as decreased hematocrit may indicate an increased risk of hematoma formation. Postoperative use of apixaban may promote the formation of ecchymoses but is not a major contributing factor.